Nutrients in ‘Opal’ apples and key metabolites in delayed browning of their pulps were analyzed based on comparative omics - WANG, Fang; LI, Rui; DING, Yuduan; TIAN, Jianwen; SHI, Xin; LI, Xiaolong LI; HUANG, Rong (Food Science and Technology, 2023)
The ‘Opal’ apple, a crossbreed between the ‘Topaz’ and ‘Golden Delicious’ varieties, has a unique crunchy, a tangy flavor, slow browning rate that can keep long-lasting freshness after being sliced up. With ‘Fuji’ apples as reference controls, the content of mineral elements, and their key metabolites in the pulps of two kinds of apples were analyzed to clarify nutritional properties and slow browning features in ‘Opal’ apples. In this study, the differential metabolites of the two cultivars of apple were statistically analyzed with the differential principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA) using UHPLC-LTQ-Orbitrap MS, combined with non-targeted metabolomics technology, to identify the key differential metabolites in the two varieties of apple. The results showed that there was a total of 147 significantly differential metabolites in 10 categories, of which phenylpropanoids and polyketides account for the highest proportion, Through KEGG pathway analysis, the differential compounds in the two apple cultivars were annotated into 52 pathways, and they were significantly enriched in the two pathways ABC transporters and Flavonoid biosynthesis. The results can lay a theoretical basis for researches on apple quality and provide data support for the indepth development of different apple products.